DINAMIKA AKUNTABILITAS DANA DESA Di ERA SUSTAINABLE DEVELOPMENT GOALs - Subhan Ilham Thareq; Gradila Apriani (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
Issues regarding the inequality of authority at the internal level of accountability organizers as well as vertically hierarchical and horizontal, as well as power relations between the community and accountability organizers give rise to anomalies in accountability practices at the village level. The purpose of this research is to analyze the dynamics of accountability in the era of Sustainable Development Goals with the bestpractice of Nangai Amen village, Lebong Regency, Bengkulu Province as the research locus, the determination of the locus is based on the village government aligning the village program with the Sustainable Development Goals, in addition, there was misappropriation of Village Funds committed by the former leadership of the village government. The type of research used used a qualitative approach. The informants were determined using a snowball technique that was closely related to the main informants in the Village Fund accountability. The findings of the research are that the involvement of many actors in the accountability mechanism creates paradoxes in the process. Political-economic intervention at the vertical level of the accountability organizing institution influences the Village Fund management policy and the accountability reporting mechanism for the use of the Village Fund. Furthermore, the overlapping authority of institutions at the horizontal level as well as, the bureaucratic aspects inherent in the accountability organizing institution add to the problems faced in the accountability process. Furthermore, the power relations between the village government and elite community groups in utilizing the Village Fund for group interests extend the dynamics of accountability in the management of the Village Fund